Thin film for improving response wave band and sensitivity of silicon detector and preparation method of thin film

By coating a thin film composed of TiO2 and MgF2 nanoparticles on the surface of the silicon detector, the light reflection problem caused by the high refractive index of the silicon detector is solved, and the photoluminescence effect of Tb3+ ions is broadened and the detector's response band is improved. Its sensitivity is achieved.

CN119521852APending Publication Date: 2025-02-25QINGHAI PROVINCIAL GEOLOGICAL SURVEY (QINGHAI PROVINCIAL INST OF GEOLOGY & MINERAL RESOURCES QINGHAI PROVINCIAL GEOLOGICAL REMOTE SENSING CENT)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411326330.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Due to the high refractive index, silicon detectors reflect more light, which reduces their sensitivity and has low response to ultraviolet light, making them unable to effectively detect ultraviolet light signals.

Method used

The film composed of TiO2 and MgF2 nanoparticles is designed to reduce the overall refractive index through the mass ratio and hollow structure of TiO2:MgF2:Tb3+, and absorb ultraviolet light through Tb3+ ions and emit visible light, thereby improving the response band and sensitivity of the silicon detector. .

Benefits of technology

It effectively reduces the reflected light on the surface of the silicon detector, improves its absorption rate to incident light, widens the response band of the detector, and significantly improves the response level in the ultraviolet light range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119521852A_ABST
    Figure CN119521852A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of photoelectric detectors, and particularly relates to a thin film for improving response wave band and sensitivity of a silicon detector and a preparation method thereof. The material comprises TiO2 nano-particles, MgF2 nano-particles and Tb < 3 + > ions, the size of the TiO2 nano-particles is 10-20 nm, the MgF2 nano-particles are of a hollow structure, the size of the MgF2 nano-particles is about 10-30 nm, the Tb < 3 + > ions are doped into crystal lattices of MgF2, the thickness of the film is 70-110 nm, and the film can reduce reflected light on the silicon surface and can convert ultraviolet light into visible light at the same time. The responsivity of the detector can be improved by reducing reflected light, and the response wave band of the silicon detector can be widened by converting ultraviolet light into visible light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The invention belongs to the field of photoelectric detection and relates to a film for improving the response band and sensitivity of a silicon detector and a preparation method thereof. Background Art Today, semiconductor materials play an important role in many fields. As a special conductive material, semiconductors have laid a solid foundation for the development of various electronic devices. Among them, photodetector materials made of semiconductors can detect and sense light signals of specific wavelengths and are widely used in industrial production and daily life [1,2]. Silicon detectors are one of the most common semiconductor photodetector materials. In addition, silicon materials have the advantages of low cost, mature technology, and good stability. It has good photoelectric responsivity in visible light and near-infrared light, and can efficiently convert optical signals into electrical signals, providing reliable technical support for image acquisition, optical communication and other fields. However, silicon has a high refractive index, which causes a large proportion of light hitting its surface to be reflected, thereby reducing the sensitivity of its detector [3]. In addition, silicon detectors have good responsiveness to visible light and near-infrared light [4,5], but low response to ultraviolet light, so they are often not used as ultraviolet detectors.

[0001] Mouritsen H,Feenders G,Liedvogel M,et al.Night-vision brain area inmigratory songbirds[J].PNAS,2005,102(23):8339-8344.

[0002] Hoogland S,Sukhovatkin V,Shukla H,et al.Megahertz-frequency large-area optical modulators at 1.55μm based on solution-cast colloidal quantumdots[J].Optics Express,2008,16(9):6683-6691.

[0003] Srivastava SK,Kumar D,Vandana,et al.Silver catalyzed nano-texturingof silicon surfaces for solar cell applications[J].Solar Energy Materials andSolar Cells,2012,100:33-38.

[0004] Van der Ende BM,Aarts L,Meijerink A.Lanthanide ions as spectralconverters for solar cells[J].Physical Chemistry Chemical Physics,2009,11(47):11081-11095.

[0005] Huang XY,Han SY,Huang W,et al.Enhancing solar cell efficiency:thesearch for luminescent materials as spectral converters[J].Chemical SocietyReviews,2013,42(1):173-201. Summary of the invention In order to overcome the disadvantages of the prior art, the present invention provides a film for improving the response band and sensitivity of a silicon detector and a preparation method thereof. The film can reduce the reflected light on the silicon surface and convert ultraviolet light into visible light. Reducing the reflected light can improve the responsiveness of the detector, and converting ultraviolet light into visible light can broaden the response band of the silicon detector. The technical solution adopted by the present invention to solve its technical problem is: Provided is a thin film for improving the response band and sensitivity of a silicon detector, comprising TiO2 nanoparticles, MgF2 nanoparticles and Tb 3+ ions, the size of the TiO2 nanoparticles is 10 to 20 nm, the MgF2 nanoparticles are hollow structures, the size is about 10 to 30 nm, the Tb 3+ ions are doped into the lattice of MgF2, and the TiO2:MgF2:Tb 3+ The mass ratio is 10:2~4:0.02~0.1. It is further preferred as a thin film for improving the response band and sensitivity of silicon detectors. Preferably, the film thickness is 70 to 110 nm. Preferably, TiO2:MgF2:Tb 3+ The mass ratio is 10:2~4:0.02~0.1. The refractive index of silicon material is about 3.4, and the refractive index of the best film to reduce its reflection is about 1.8, which is obtained from Fresnel's reflection law. However, the refractive index of TiO2 bulk is 2.4, and the refractive index of MgF2 bulk is 1.38. Hollow MgF2 can further reduce its refractive index. According to the combination of TiO2 and MgF2 particles, the overall refractive index can be reduced to about 1.8. In addition, TiO2 and MgF2 are both nanoparticles, which can be purified by centrifugation, washing and purification. Then the coated film does not need annealing. Tb 3+ Ions can absorb ultraviolet light in the 320-400nm band and emit visible light around 544nm, which can convert ultraviolet light into visible light that silicon detectors can easily respond to. The film needs to have a certain film thickness to reduce light reflection. The above film thickness satisfies the Fresnel reflection law and is the optimal film thickness. The present invention also provides a method for preparing a thin film for improving the response band and sensitivity of a silicon detector, comprising the following steps: S1. Preparation of TiO2 nanoparticles: 18-24 g of titanium sulfate was added to 40-60 mL of deionized water, and stirred continuously for 30 min. Then, the mixture was poured into polytetrafluoroethylene and placed in a reactor. The mixture was heated at 100-150° C. for 6-12 h. After the reaction was completed, the mixture was cooled to room temperature and washed by centrifugation to obtain TiO2 nanoparticles. S2, MgF2 doped Tb 3+ Preparation of nanoparticles: 12-16g of magnesium acetate tetrahydrate (Mg(CH3COO)2·4H2O), 0.12-0.4g of terbium nitrate hexahydrate (Tb(NO3)3·6H2O) and 40-60mL of n-propanol were stirred vigorously at room temperature. Then 4-6mL of hydrofluoric acid was added and stirred for 30min, and then 4-6mL of hydrochloric acid and 1-3mL of deionized water were added. Stirred for 1-2h. Then poured into polytetrafluoroethylene and placed in a reactor, heated at 160-200℃ for 3-6h. After the reaction was completed, it was cooled to room temperature and centrifuged and washed to obtain MgF2-doped Tb 3+ Nanoparticles; S3, preparing composite sol: 1g of TiO2 nanoparticles described in step S1 and 0.2-0.4g of MgF2 doped with Tb in step S2 3+ The nanoparticles are added into 60-100 mL of anhydrous ethanol and stirred to obtain a composite sol; S4. Apply the sol obtained in step S3 on the surface of the silicon detector to obtain a thin film. It is a further preferred method for preparing a thin film for improving the response band and sensitivity of a silicon detector. Preferably, the coating method in step S4 is an immersion pulling method, and the pulling speed is 75-150 mm / min. The pulling speed can control the thickness of the film, and the speed is proportional to the film thickness. Compared with the prior art, the present invention has the following beneficial effects: (1) Compared with the prior art, the thin film prepared by the present invention can reduce the reflected light on the surface of the silicon detector, so that the silicon detector absorbs more incident light and improves its detection rate. (2) The single-layer film can not only reduce the reflection of light, but also broaden the response band of the silicon detector. In the prior art, the response band of the silicon detector to ultraviolet light is relatively low, while the present invention improves its responsiveness to ultraviolet light by converting ultraviolet light into visible light. (3) The present invention also selects suitable particles as materials for preparing thin films. The proportion of the particles directly affects the performance of reducing light reflection. In addition, MgF2 is easily doped with rare earth ions so that the MgF2 particles have photoluminescent properties. The hollow structure of MgF2 nanoparticles has a very low refractive index. After mixing with TiO2 particles, the overall refractive index of the coating can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 (a) is a transmission electron microscope photograph of the TiO2 nanoparticles in Example 1, Figure 1 (b) is the particle size statistics and Gaussian fitting curve; Figure 2 (a) is the MgF2 doped Tb in Example 1 3+ Transmission electron micrograph of nanoparticles of particles, Figure 2 (b) is the particle size statistics and Gaussian fitting curve. Figure 2 (c) is a high-resolution transmission electron microscope photo. Figure 2 (d) is the MgF2 doped Tb in Example 1, Example 6 and Example 7 3+ Fluorescence spectra of ionic nanoparticles; Figure 3 is a scanning electron microscope photograph of the silicon detector substrate and the film in Example 1; Figure 4 is the current response curve of the silicon detector in the comparative example and embodiments 1 to 5 under 350nm pulse light; Figure 5 is the reflectivity curve of the silicon detector surface in the comparative example and embodiments 1 to 5; Figure 6 It is the IV curve of the silicon detector in the comparative example and Examples 1 to 5. DETAILED DESCRIPTION The present invention will be further described below in conjunction with comparative examples and embodiments. Comparative Example Silicon detector without any surface treatment. Example 1 This embodiment provides a method for preparing a thin film for improving the response band and sensitivity of a silicon detector, comprising the following steps: S1. Preparation of TiO2 nanoparticles: 18 g of titanium sulfate was added to 40 mL of deionized water, stirred continuously for 30 min, then poured into polytetrafluoroethylene and placed in a reactor, heated at 100 °C for 6 h, cooled to room temperature after the reaction, and obtained TiO2 nanoparticles by centrifugal washing; S2, MgF2 doped Tb 3+ Preparation of nanoparticles: 12g of magnesium acetate tetrahydrate (Mg(CH3COO)2·4H2O), 0.12g of terbium nitrate hexahydrate (Tb(NO3)3·6H2O) and 40mL of n-propanol were stirred vigorously at room temperature, and then 4mL of hydrofluoric acid was added and stirred for 30min. Then 4mL of hydrochloric acid and 1mL of deionized water were added and stirred for 1h. Then, the mixture was poured into polytetrafluoroethylene and placed in a reactor. The mixture was heated at 160℃ for 3h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain MgF2-doped Tb 3+ Nanoparticles; S3, preparing composite sol: 1g of TiO2 nanoparticles described in step S1 and 0.2g of MgF2 doped Tb described in step S2 3+ The nanoparticles were added into 60 mL of anhydrous ethanol and stirred to obtain a composite sol; S4. The composite sol obtained in step S3 is coated on the surface of the silicon detector by dipping and pulling at a pulling speed of 93.8 mm / min to obtain a thin film. The thin film obtained in this embodiment is composed of TiO2, MgF2 and Tb 3+ The composition has a mass ratio of 10:2:0.02, and the thickness of the film is about 80nm. Embodiments 2 to 5 The difference between Examples 2 to 5 and Example 1 is that the pulling speeds of the immersion pulling are 75 mm / min, 112.5 mm / min, 130.9 mm / min and 150 mm / min, respectively, and the corresponding film thicknesses are 70 nm, 90 nm, 100 nm and 110 nm, respectively. Example 6 This embodiment provides a method for preparing a thin film that improves the response band and sensitivity of a silicon detector. S1. Preparation of TiO2 nanoparticles: 24 g of titanium sulfate was added to 60 mL of deionized water, stirred continuously for 30 min, then poured into polytetrafluoroethylene and placed in a reactor, heated at 150° C. for 12 h, cooled to room temperature after the reaction, and obtained TiO2 nanoparticles by centrifugal washing; S2, MgF2 doped Tb 3+ Preparation of nanoparticles: 16g of magnesium acetate tetrahydrate (Mg(CH3COO)2·4H2O), 0.4g of terbium nitrate hexahydrate (Tb(NO3)3·6H2O) and 60mL of n-propanol were stirred vigorously at room temperature, and then 4-6mL of hydrofluoric acid was added and stirred for 30min, and then 6mL of hydrochloric acid and 3mL of deionized water were added and stirred for 2h. Then, the mixture was poured into polytetrafluoroethylene and placed in a reactor, and heated at 200℃ for 6h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged and washed to obtain MgF2-doped Tb 3+ Nanoparticles; S3, preparing composite sol: 1g of TiO2 nanoparticles described in step S1 and 0.0.4g of MgF2 doped Tb described in step S2 3+ The nanoparticles were added into 100 mL of anhydrous ethanol and stirred to obtain a composite sol; S4. The composite sol obtained in step S3 is coated on the surface of the silicon detector by dipping and pulling at a pulling speed of 112.5 mm / min to obtain a thin film. The thin film obtained in this embodiment is composed of TiO2, MgF2 and Tb 3+ The composition has a mass ratio of 10:4:0.1 and the thickness of the film is about 90nm. Example 7 This embodiment provides a method for preparing a thin film that improves the response band and sensitivity of a silicon detector. S1. Preparation of TiO2 nanoparticles: 20 g of titanium sulfate was added to 50 mL of deionized water, stirred continuously for 30 min, then poured into polytetrafluoroethylene and placed in a reactor, heated at 120 °C for 8 h, cooled to room temperature after the reaction, and obtained TiO2 nanoparticles by centrifugal washing; S2, MgF2 doped Tb 3+Preparation of nanoparticles: 12g of magnesium acetate tetrahydrate (Mg(CH3COO)2·4H2O), 0.3g of terbium nitrate hexahydrate (Tb(NO3)3·6H2O) and 50mL of n-propanol were stirred vigorously at room temperature, and then 5mL of hydrofluoric acid was added and stirred for 30min. Then 5mL of hydrochloric acid and 2mL of deionized water were added and stirred for 2h. Then, the mixture was poured into polytetrafluoroethylene and placed in a reactor. The mixture was heated at 180℃ for 4h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged and washed to obtain MgF2-doped Tb 3 + Nanoparticles; S3, preparing composite sol: 1g of TiO2 nanoparticles described in step S1 and 0.3g of MgF2 doped Tb described in step S2 3+ The nanoparticles were added into 80 mL of anhydrous ethanol and stirred to obtain a composite sol; S4. The composite sol obtained in step S3 is coated on the surface of the silicon detector by dipping and pulling at a pulling speed of 112.5 mm / min to obtain a thin film. The thin film obtained in this embodiment is composed of TiO2, MgF2 and Tb 3+ The composition has a mass ratio of 10:3:0.075, and the thickness of the film is about 90nm. Figure 1 (a) is a transmission electron microscope photograph of the TiO2 nanoparticles in Example 1, Figure 1 (b) is the particle size statistics and Gaussian fitting curve. It can be seen that the particle size distribution of TiO2 is 10-20nm. Figure 2 (a) is the MgF2 doped Tb in Example 1 3+ Transmission electron micrograph of nanoparticles of ions. Figure 2 (b) is the particle size statistics and Gaussian fitting curve. 3+ The size distribution of the ionic nanoparticles is 10 to 30 nm. Figure 2 (c) is a high-resolution transmission electron microscope photo, showing that MgF2 doped with Tb 3+ Ionic nanoparticles have a hollow structure. Figure 2 (d) is the MgF2 doped Tb in Example 1, Example 6 and Example 7 3+ The fluorescence spectrum of the nanoparticles of ions. This shows that the synthesized particles can convert ultraviolet light before 350nm into visible light around 544nm. And it can be seen that Tb 3+ The more ions are doped, the stronger the fluorescence intensity is. Figure 3This is a scanning electron microscope photo of the silicon detector substrate and film in Example 1. It can be seen that the composite particle film is coated on the silicon detector. Figure 4 The current response curves of the silicon detectors in the comparative example and Examples 1 to 5 under 350nm pulse light are shown. It can be seen that the responsivity of the silicon detector without coating under 350nm ultraviolet light is significantly lower than that of the silicon detector after coating. This is because the coating can convert ultraviolet light into visible light, thereby improving the responsivity of the ultraviolet light part. Figure 5 The reflectivity curves of the silicon detector surface in the comparative example and Examples 1 to 5 are shown. It can be seen that after coating, the reflected light on the silicon detector surface is significantly reduced, and the position of the lowest point of the reflectance value is related to the thickness of the film. Reducing the reflected light can increase the silicon detector's absorption of light. Figure 6 The IV curves of the silicon detectors in the comparative examples and embodiments 1 to 5 are shown. It can be seen from the comparative examples and embodiments that the short-circuit current and open-circuit voltage of the IV curve of the silicon detector after coating are higher than those without coating. This is because the coating can reduce the reflection of light and convert ultraviolet light into visible light, thereby improving the response of the detector. In summary, the film can reduce the reflected light on the silicon surface and convert ultraviolet light into visible light. Reducing the reflected light can improve the detector's responsivity, while converting ultraviolet light into visible light can broaden the silicon detector's response band. Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A thin film for improving the response band and sensitivity of a silicon detector, characterized in that: Including TiO2 nanoparticles, MgF2 nanoparticles and Tb 3+ ions, the size distribution of the TiO2 nanoparticles is 10 to 20 nm, the MgF2 nanoparticles are hollow structures with a size distribution of 10 to 30 nm, and the Tb 3+ Ions are doped into the lattice of MgF2.

2. The thin film for improving the response band and sensitivity of silicon detector according to claim 1, characterized in that: The thickness of the film is 70 to 110 nm.

3. The thin film for improving the response band and sensitivity of silicon detector according to claim 1, characterized in that: TiO2:MgF2:Tb 3+ The mass ratio is 10:2~4:0.02~0.

1.

4. A method for preparing a thin film for improving the response band and sensitivity of a silicon detector as claimed in claims 1 to 3, characterized in that: The following steps are involved: S1. Preparation of TiO2 nanoparticles: 18-24 g of titanium sulfate was added to 40-60 mL of deionized water, and stirred continuously for 30 min. Then, the mixture was poured into polytetrafluoroethylene and placed in a reactor. The mixture was heated at 100-150° C. for 6-12 h. After the reaction was completed, the mixture was cooled to room temperature and washed by centrifugation to obtain TiO2 nanoparticles. S2, MgF2 doped Tb 3+ Preparation of nanoparticles: 12-16 g of magnesium acetate tetrahydrate (Mg(CH3COO)2·4H2O), 0.12-0.4 g of terbium nitrate hexahydrate (Tb(NO3)3·6H2O) and 40-60 mL of n-propanol were stirred vigorously at room temperature, and then 4-6 mL of hydrofluoric acid was added and stirred for 30 min. Then 4-6 mL of hydrochloric acid and 1-3 mL of deionized water were added and stirred for 1-2 h. Then, the mixture was poured into polytetrafluoroethylene and placed in a reactor. The mixture was heated at 160-200 ° C for 3-6 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged and washed to obtain MgF2-doped Tb 3+ Nanoparticles; S3, preparing composite sol: 1g of TiO2 nanoparticles described in step S1 and 0.2-0.4g of MgF2 doped with Tb in step S2 3+ The nanoparticles are added into 60-100 mL of anhydrous ethanol and stirred to obtain a composite sol; S4. Apply the composite sol obtained in step S3 on the surface of the silicon detector to obtain a thin film.

5. The method for preparing a thin film for improving the response band and sensitivity of a silicon detector according to claim 4, characterized in that: The coating method in step S4 is a dipping and pulling method, and the pulling speed is 75-150 mm / min.